Factors influencing the progression from prehypertension to hypertension among Chinese middle-aged and older adults: a 2-year longitudinal study - Zhen Li; Lianmeng Cao; Ziyu Zhou; Maozhi Han; Chang Fu (BMC, 2023)
Abstract Background This study aimed to investigate the proportion of prehypertension cases progressing to hypertension among Chinese middle-aged and elderly populations over a 2-year period and related influencing factors. Methods Data were obtained from the China Health and Retirement Longitudinal Study, and 2,845 individuals who were ≥ 45 years old and prehypertensive at baseline were followed from 2013-2015. Structured questionnaires were administered, and blood pressure (BP) and anthropometric measurements were performed by trained personnel. Multiple logistic regression analysis was done to investigate factors associated with prehypertension progressing to hypertension. Results Over the 2-year follow-up, 28.5% experienced progression of prehypertension to hypertension; this occurred more frequently in men than women (29.7% vs. 27.1%). Among men, older age (55-64 years: adjusted odds ratio [aOR] = 1.414, 95% confidence interval [CI]:1.032-1.938; 65-74 years: aOR = 1.633, 95%CI: 1.132-2.355; ≥ 75 years: aOR = 2.974, 95%CI: 1.748-5.060), obesity (aOR = 1.634, 95%CI: 1.022-2.611), and number of chronic diseases (1: aOR = 1.366, 95%CI: 1.004-1.859; ≥ 2: aOR = 1.568, 95%CI: 1.134-2.169) were risk factors for progression to hypertension whereas being married/cohabiting (aOR = 0.642, 95% CI: 0.418-0.985) was a protective factor. Among women, risk factors included older age (55-64 years: aOR = 1.755, 95%CI: 1.256-2.450; 65-74 years: aOR = 2.430, 95%CI: 1.605-3.678; ≥ 75 years: aOR = 2.037, 95% CI: 1.038-3.995), married/cohabiting (aOR = 1.662, 95%CI: 1.052-2.626), obesity (aOR = 1.874, 95%CI: 1.229-2.857), and longer naps (≥ 30 and < 60 min: aOR = 1.682, 95%CI: 1.072-2.637; ≥ 60 min: aOR = 1.387, 95%CI: 1.019-1.889). Conclusions Chinese middle-aged and elderly individuals experienced a risk of prehypertension progressing to hypertension over a 2-year period, although the influencing factors differed by sex; this should be considered in interventions.